Sistem Pendidikan di Jepang dan Korea Selatan - Susi Eka Ningsih; Khairul Anisa; Mislaini Mislaini (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This paper aims to describe (tell) about the education system in Japan and South Korea. This study uses library research methodology, and is qualitative, because the data collection obtained uses textual analysis found in books related to the ethics of the education system in Japan and South Korea. The results of this study are first The results of the literature review conducted by the author that the success and progress in Japan are character. The character culture of Japanese society is formed through moral education from elementary school to college. Second Education used to be very low in South Korea because it was taken over by Japan. South Korea made key policies to achieve educational development and economic growth simultaneously.